2019
DOI: 10.1093/jas/skz258.835
|View full text |Cite
|
Sign up to set email alerts
|

PSXII-34 Narasin improves performance of grazing Nellore yearling bulls receiving protein supplement

Abstract: The objective of this trial was to determine the effect of narasin inclusion into a protein supplement on the performance of grazing yearling bulls. One hundred and fifty Nellore yearling bulls were blocked by initial BW (332 ± 3.4 kg) and assigned to 30 paddocks (15 paddocks/treatment). Sixty paddocks of Brachiaria brizantha with 1 ha each were used, whereas each paddock was continuously grazed by 28 d, followed by a resting period of 28 d. Paddocks were rotated among treatments every 28 d to minimize possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Daily supplementation of narasin increased ruminal propionate and SCFA concentration and reduced Ac:Prop ratio in beef cattle fed forage-based diets ( Miszura et al, 2019 ; Polizel et al, 2020 ; Limede et al, 2021 ). Additionally, daily supplementation of narasin into low-consumption mineral and protein supplements benefited performance in grazing cattle ( Polizel et al, 2017 , 2018 , 2019 ), given these supplements are often consumed erratically by animals ( Cappellozza et al, 2019 ), denoting a possible lasting effect of this molecule on ruminal metabolism. In fact, even after the removal of ionophores from the diet, there is still a residual effect on ruminal environment and fermentation parameters of steers consuming forage-based diets ( Bell et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Daily supplementation of narasin increased ruminal propionate and SCFA concentration and reduced Ac:Prop ratio in beef cattle fed forage-based diets ( Miszura et al, 2019 ; Polizel et al, 2020 ; Limede et al, 2021 ). Additionally, daily supplementation of narasin into low-consumption mineral and protein supplements benefited performance in grazing cattle ( Polizel et al, 2017 , 2018 , 2019 ), given these supplements are often consumed erratically by animals ( Cappellozza et al, 2019 ), denoting a possible lasting effect of this molecule on ruminal metabolism. In fact, even after the removal of ionophores from the diet, there is still a residual effect on ruminal environment and fermentation parameters of steers consuming forage-based diets ( Bell et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Narasin is an ionophore that improves performance of grazing beef cattle without affecting mineral ( Silva et al, 2015 ) or protein supplement intake ( Polizel et al, 2019 ). Daily supplementation of narasin to beef cattle fed forage-based diets increased concentration of ruminal propionate and total short-chain fatty acids (SCFA) and reduced acetate:propionate (Ac:Prop) ratio ( Miszura et al, 2019 ; Polizel et al, 2020 ; Limede et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies were carried out with the objective of evaluating the effects of narasin in diets containing high forage content. Polizel et al (2019) evaluating the ruminal fermentation parameters of cattle fed high roughage diets receiving control (no narasin), 13 mg/kg DM and 20 mg/kg DM of narasin, observed that narasin doses increased the molar proportion of propionate, decreased acetate, and consequently altered the acetate:propionate ratio. These changes in rumen fermentation parameters were obtained when narasin was supplied once a day (every 24 hours).…”
Section: Metabolismmentioning
confidence: 99%
“…There was no interaction between treatment and period for ADG and DMI, however, the inclusion of narasin in mineral salt did not affect DMI and increased ADG and final body weight. Polizel et al (2019) evaluated the effect of narasin on protein supplementation on the performance of Brachiaria brizantha grazing bulls. The experimental treatments were control (no additive inclusion) and the inclusion of 13 ppm narasin.…”
Section: Performancementioning
confidence: 99%